2011
DOI: 10.26719/2011.17.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Association of myocardial infarction with stressful life events and psychiatric symptoms: a population based survey

Abstract: Psychosocial factors such as depression, hostility, social isolation are associated with increased risk of coronary heart disease. We aimed to determine the association of psychiatric symptoms and psychosocial factors with myocardial infarction (MI). We performed a secondary analysis of data from a population-based survey of Iranians aged 18-65 years using standardized psychosocial instruments. Of the 2158 participants, 51 had suffered an MI. In univariate analysis: number of stressful life events, stressfulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Countries in Eastern Europe show a disproportionately high burden of IHD [ 17 ]. This high burden is difficult to attribute to any single factor, however, lifestyle, social stress, and alcoholism have been implicated [ 17 , 21 - 22 ]. In certain countries, the increased current burden could be attributed to changing population distributions [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Countries in Eastern Europe show a disproportionately high burden of IHD [ 17 ]. This high burden is difficult to attribute to any single factor, however, lifestyle, social stress, and alcoholism have been implicated [ 17 , 21 - 22 ]. In certain countries, the increased current burden could be attributed to changing population distributions [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation has been identified as a risk factor for incident CVD [43]. Furthermore, SI [126] in CVD patients has been associated with increased recurrent cardiac morbidity and mortality, and accelerated development of carotid atherosclerosis is seen in isolated CVD patients [104].…”
Section: Part Iii: Isolation As a Factor In Cardiovascular Disease Anmentioning
confidence: 99%
“…[18] We recently found that self-reported stressful life events in the past year were independently associated with increased risk of future falls in older men. [9] Though we also found that stressful life events increased age-adjusted risk for incident clinical fracture nearly 60%, these results were attenuated and no longer statistically significant after additional adjustment for a one-time measurement of bone mineral density (BMD) and other factors.…”
Section: Introductionmentioning
confidence: 99%